Frederick Taylor as a Contributor to Public Administration - Myrick, Darrell (Mediterranean Journal of Social Sciences, 2012)
Seventy-five years after his death, a question remains as to whether Frederick Taylor’s scientifictheories of management have made a significant contribution to Public Administration. Taylor’stheories focused mainly on increasing productivity in industrial manufacturing environments. Theprimary concern was for a pragmatic approach to efficiency where planning and standardisationaimed to optimise the human element in production. The article examines how practitioners of PublicAdministration have adopted and implemented Taylor’s theories. Evidence was found in the work ofMorris Cooke, a Taylor disciple who focused on public sector oriented approaches to management andpolitical economy. Taylorism was apparent in the public sector in the years after World War II, aturning point and period when Taylorist theories were humanised. The aim of the article then is toexamine how Public Administration has drawn from the field of industrial psychology, towardsimproving operations in public organisations. The key question is: to what extent has industrialscientific management principles been adopted in the discipline of Public Administration? In light ofpoor service delivery in South Africa, it is a relevant question that has implications for improvingoperational efficiency. A historical literature review was undertaken to determine the influence ofTaylor’s scientific management theories on Public Administration. The findings drawn from this reviewand analysis will serve to inform the need for more orderly scientific approaches to service delivery.